2012
DOI: 10.1021/ja211765y
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Reduction of a Layered Metal Chalcogenide into a 1D Near-IR Direct Band Gap Semiconductor

Abstract: Reducing the dimensionality of inorganic lattices allows for the creation of new materials that have unique optoelectronic properties. We demonstrate that a layered metal chalcogenide lattice, TiS(2), can form a dimensionally reduced crystalline one-dimensional hybrid organic/inorganic TiS(2)(ethylenediamine) framework when synthesized from molecular precursors in solution. This solid has strong absorption above 1.70 eV and pronounced emission in the near-IR regime. The energy dependence of the absorption, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 32 publications
4
45
1
Order By: Relevance
“…The determined valence band onset value seems to be inconsistent with some previous reports, where TiS 2 bandgap was determined to be 0.7 eV or lower . However, several theoretical and experimental reports suggest that E g of nanostructured TiS 2 could be tuned by changing its morphology (i.e., from nanotubes to single‐sheet monolayers), leading to semimetal‐to‐semiconductor transition . In our case, the determination of the VBM is quite involved as some tailing intensity extends up to the Fermi level, which could be consistent with bulk TiS 2 having a semimetallic character as already proposed, and defect‐rich TiO 2 can also contribute to this density of states.…”
Section: Resultscontrasting
confidence: 92%
“…The determined valence band onset value seems to be inconsistent with some previous reports, where TiS 2 bandgap was determined to be 0.7 eV or lower . However, several theoretical and experimental reports suggest that E g of nanostructured TiS 2 could be tuned by changing its morphology (i.e., from nanotubes to single‐sheet monolayers), leading to semimetal‐to‐semiconductor transition . In our case, the determination of the VBM is quite involved as some tailing intensity extends up to the Fermi level, which could be consistent with bulk TiS 2 having a semimetallic character as already proposed, and defect‐rich TiO 2 can also contribute to this density of states.…”
Section: Resultscontrasting
confidence: 92%
“…Similarly, we found that long‐chain amines played a key role in the formation of superlattices, which is indirectly evidenced by the tunable periodicities ranging from 2.8 to 5.3 nm with different amines as structure‐directing agents. This structure‐directing effect of amines can also be found in many literatures, in which amine molecules acted as linkers to bridge semiconductor atomic layers, forming periodic 3D lattices . In our case, the ZnS superlattices are directed by the long‐chain amines that are usually used in the synthesis and self‐assembly of NCs .…”
Section: Methodssupporting
confidence: 69%
“…5−8 Indeed, dimensionally reduced solids have been discovered from the perovskite lattice, 9,10 zinc blende/wurtzite lattice, 11 two-dimensional (2D) metal chalcogenide lattice, 12,13 and layered iron selenide lattice. 14 These dimensionally reduced phases are thermodynamically stable because, for a set of metal cations and anions with specific oxidation states, there is some inherent stability for a specific type of polyhedral shape and connectivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The most common approaches deliver molecular precursors of the metal and anion in the appropriate oxidation states in the presence of organic terminating ligands. 12,23 Here a large parameter space exists, including ligand choice, ligand-tometal ratio, and reaction temperature. It is unclear how these parameters can be tuned to access the dimensionally reduced phases in favor of the parent material.…”
Section: ■ Introductionmentioning
confidence: 99%